La La función del compliance en el análisis de la responsabilidad penal de la persona jurídica - Raza Castañeda, Stalin (2016)
The following essay will contain 6 fundamental aspects: 1. A theoretical and practical approach to the state of art for attributing criminal responsibility to legal entities. 2. How attributing criminal resposibility to legal entities is compatible with law governed constitutional democracies. 3. The known models of attributing criminal responsibility to legal entities. 4. An analysis of the conflict between attributing criminal responsibility to legal entities and the existing structure of criminal law and criminal procedures. 5. Compliance’s role in determining criminal responsibility to legal entities. 6. An evaluation of whether or not it is necessary to improve the structure of criminal law and criminal procedures so that they can be applied in affairs of criminal responsibility to legal entities; and if it is the case, how compliance will support the new structure